Answer:
a) The quotient rule is:
if: f(x) = 1/g(x)
Then:
[tex]f'(x) = -\frac{1}{(g(x))^2}*g'(x)[/tex]
In this case, we have:
G(x) = 1/x
Then we can write this as:
G(x) = 1/h(x) with h(x) = x, and h'(x) = 1
Using the above rule we get:
G'(x) = -(1/h(x)^2)*h'(x) = -1/x^2
b) For a function like:
f(x) = x^n
we have that:
[tex]f'(x) = n*x^{n - 1}[/tex]
Here we can write G(x) = x^-1
Then we have n = -1
If we use the above rule, we get:
[tex]G'(x) = (-1)*x^{-1-1} = -1*x^{-2} = \frac{-1}{x^2}[/tex]
So we got the same result using both methods.